Qualidade do solo em sistema de pastagem convertida ao cultivo de dendê (Elaeis guineenses Jacq.) - Maldonado, Selvin Antonio Saravia (2017)
The oil palm is a crop that has great economic potential, since its producti ve potential is extremely high, being culti vated in several countries of Asia, Africa and America. In Brazil, its culti vation is concentrated in only a few regions, distributed mai nly in the Northeast and North of the country. However, in spite of the few areas with commercial culti vation, the oil palm presents potential of planting due to the advantage of being able to intercalate different species, with emphasis on the recovery of altered areas and forest fragments. The objecti ve of this work was to study the soil quality in a pasture system converted to palm oil (Elaeis guineenses Jacq.), Under i ntercropping, established in an experimental area of Embrapa, i n the municipality of São João da Baliza, Boa Vista - RR, vicinal 26, Km 12, with geographic reference coordi nates 00º 51' 13,3''N and 60º 00' 19,8''W and an altitude of 100 m, i nstalled on a Red-Yellow Argisol. The planting systems had dimensions of 36 mx 39 m, formi ng a total area of 1,404 m². The experimental design was completely randomi zed, in a subdi vided plots scheme with 4 replicates for the chemical and physical analyzes, and completely randomi zed with 4 replicates for the microbiological and biochemical analyzes. The treatments consisted of 5 systems intercalated with palm, being: 1) i ntercalated with grass, Brachiaria h umidicola (DP); 2) pineapple, C v. Victory (DA); 3) Cowpea, Cv. Guariba (DF); 3) banana, Cv. Japira (DB); 4) cassava, C v. Amazonas (DM) and 5) grass, Brachiaria humidicola (PS). The physical and chemical attributes were evaluated in the layers 0-0.10 ; 0.10-0.30 and 0.30-0.50 m and i n the 0-0.10 m layer for the microbiological and biochemical attributes. It was found a heavier granulometry for the DM, DB and P systems which in turn presented higher formation and stabilization of aggregates denoted by high DMG, DMP and IS i ndexes, covering all this, under balanced macro and micropore conditions, i ncreases in total porosity and decrease of soil density. The highest values of pH, exchangeable Ca2+, Mg2+, K+ and the decrease of Al3+ i n the DM e DF intercalations s ystems were observed for all the layers evaluated, with high levels in the sorption complex, SB, C TCt and V. The area PS presented low ferti lity, originating from its natural conditions. Meanwhile, the systems that showed the best results and that contributed most to improve the soil microbiological and biochemical conditions were PS, DP and DM, positi vely influencing variables C-BMS, qCmic and the enzymatic activities of β-glucosidase, urease and acid phosphatase.